The Effect Of Physical Fitness Component On Some Athletics Events During Menstruation and Nonmenstruation Days In female College of Physical Education and Sport Sciences' Students - Mounir, Yessar (Journal of Physical Education, 2018)
The Effect Of Physical Fitness Component On Some Athletics Events During Menstruation and Nonmenstruation Days In female College of Physical Education and Sport Sciences' StudentsThe problem of the research lies in the lack of scientific researches that study the effect of menstruation on athletics events and fitness components. The aim of this research was to study some physical fitness components in running, jumping and throwing events before – during and after menstruation in female students. The research was conducted on Tikreet University female students of physical education and sport Sciences College. Two pilot study were conducted to specify three phases; the first phase 2 – 3 days before menstruation, 2nd phase 2 – 3 days during menstruation, and 3rd phase 7 – 8 days of menstruation. All tests were conducted during all phases to collect the data that was treated using SPSS. The researcher concluded that there is a decrease in muscular flexibility of arms and legs, general stamina of cardiovascular and respiratory systems during the 7th day of menstruation. There are no differences in explosive power, strength – speed, maximal transitional speed, and agility. There is a decrease in 100m running achievement while no differences are found in long jump and discus throwing. The researcher recommended paying attention to female students during menstruation especially concerning general stamina and muscular flexibility when planning training loads as well as making similar studies on other age groups and on other subjects.